The Use of Short Stories on Wattpad to Boost Students Reading Comprehension Achievement - Sari, Alya Rahma; Permana, Dio Resta; Anggraini, Dita Rizki (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
Difficulties in processing information from English texts could hinder the learning process and negatively impact students' academic achievement. Therefore, the purpose of this study was to analyze the use of short stories on Wattpad in improving the reading comprehension achievement of ninth-grade students at SMP Negeri 19 Palembang and students' perceptions of using short stories on Wattpad. This research used a pre-experimental design with a sample of class 9.3 consisting of 31 students. Data collection was carried out using pre-tests and post-tests, which were analyzed using paired sample t-tests and N-Gain scores with the help of the SPSS version 29. The findings were indicating an increase in students' reading comprehension achievement. Additionally, experimental students were giving a positive perception of the use of short stories on Wattpad in the learning process.